2018
DOI: 10.1177/000313481808400520
|View full text |Cite
|
Sign up to set email alerts
|

Management of Esophageal Perforation: 28-Year Experience in a Major Referral Center

Abstract: Esophageal perforation constitutes a surgical emergency. Despite its gravity, no single strategy has been described as sufficient to deal with most situations to date. The aim of this study was to assess the etiology, management, and outcome of esophageal perforation over a 28-year period, to characterize optimal treatment options in this severe disease. A retrospective clinical review of all patients treated for esophageal perforation at Ramón y Cajal Hospital between January 1987 and December 2015 was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Third, although we believed that it was important to evaluate the incidence of esophageal perforation (a potentially catastrophic complication directly attributable to TEE), TEE is not the only cause of iatrogenic esophageal perforation. 65 Nasogastric or orogastric tube placement and upper gastrointestinal endoscopic procedures may result in iatrogenic esophageal perforation after cardiac surgery. 66,67 Thus, because the observed rate of esophageal perforation was <0.01%, and equal across both groups, we were statistically underpowered to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although we believed that it was important to evaluate the incidence of esophageal perforation (a potentially catastrophic complication directly attributable to TEE), TEE is not the only cause of iatrogenic esophageal perforation. 65 Nasogastric or orogastric tube placement and upper gastrointestinal endoscopic procedures may result in iatrogenic esophageal perforation after cardiac surgery. 66,67 Thus, because the observed rate of esophageal perforation was <0.01%, and equal across both groups, we were statistically underpowered to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the majority of patients (58.3%) who died during hospital stay showed ruptures in the distal part of the esophagus followed by patients (33.3%) with ruptures in the middle third of the esophagus, although no significant correlation with mortality was observed. On the contrary, other studies have shown that mortality rates are higher in patients with perforations in the middle and distal part of the esophagus [1,2,8,17]. However, none of the studies excluded patients with esophageal malignancies, which commonly arise in the distal third of the esophagus.…”
Section: Discussionmentioning
confidence: 98%
“…The most common causes of esophageal perforations are iatrogenic and Boerhaave's syndrome. The etiology of the perforation determines its location in the esophagus and influences clinical symptoms, which vary and are non-specific [1,2]. The extent of mediastinal or pleural contamination is determined by computed tomography [3].…”
Section: Introductionmentioning
confidence: 99%
“…Referred to as Boerhaave syndrome, spontaneous perforation occurs when intraesophageal pressure rises in the face of low intrathoracic pressure, most commonly due to forceful retching and vomiting. Most perforations occur in the distal intrathoracic or abdominal esophagus, and a timely diagnosis relies on a high index of clinical suspicion, along with confirmatory laboratory, radiographic, and/or endoscopic findings [1,2]. Immediate management options include close medical observation or surgical and endoscopic therapies to either repair the defect or prevent further extravasation of luminal contents into the mediastinum or pleural spaces.…”
mentioning
confidence: 99%
“…The type of intervention typically depends on the patient's clinical stability, the size and location of the lesion, and a variety of other host factors. If appropriate medical and surgical interventions are performed within the first 24 hours, the 30-day in-hospital mortality rate is below 8%, but with delays, the mortality rate rises above 20% [1][2][3]. Stratified by location, abdominal perforations carry the highest mortality rate, exceeding 13% [1].…”
mentioning
confidence: 99%